Determinants of Profitability in Indonesian Islamic Banks - Triadi Septian Anugra; Fathihani Fathihani; Ika Puji Saputri (Institute of Advanced Knowledge and Science, 2025)
This study aims to analyze the effect of Capital Adequacy Ratio (CAR), NonPerforming Financing (NPF), Operating Costs to Operating Income (BOPO), and Financing to Deposit Ratio (FDR) on the profitability of Islamic commercial banks for the period 2019–2023. A quantitative approach is used, using secondary data sourced from the annual financial reports of 12 Islamic banks registered with the Financial Services Authority (OJK). The research findings reveal that CAR has a significant positive effect on ROA, indicating that higher capital buffers increase profitability. Conversely, NPF has a negative impact on ROA, highlighting the adverse impact of credit risk on bank performance. BOPO has a significant negative impact on ROA, emphasizing the importance of operational efficiency in increasing profitability. FDR shows a positive and significant relationship with ROA. These findings provide practical insights for bank management and regulators to improve operational efficiency and credit quality, which ultimately supports the sustainable growth of Islamic banking in Indonesia.